TECHNICAL ASPECTS AND COSTS BENEFITS OF THE MODEL MANGROVES - SHRIMP IN NAM CAN DISTRICT, CA MAU PROVINCE - Viet, Le Quoc; Hai, Tran Ngoc (Vietnam Journal of Marine Science and Technology, 2016)
The study was conducted from August to December 2014. Thirty seven mangroves-shrimp farmers in Nam Can district, Ca Mau were randomly selected for the interview. The aim of this study was to assess the costs and benefits and to identify the factors affecting the model. The results showed that the average of farm area was 2.1 ha, with forest cover of 35.9%, and water depth in ditch of 1.3 m, and in marsh land of 0.5 m. The age of tree was 2 to 17 years (6.7 years in average). The stocking time for shrimp and crab was 4.7 and 5.2 times/year respectively; and stocking density was 16.8 shrimp/m2 and 0.6 crabs/m2. The shrimp and crab survival rate was 1.3% and 3.8%, respectively. The average yields of black tiger shrimp, crab, natural shrimp and fish were 196 kg/ha/year, 61 kg/ha/year, 89 kg/ha/year and 71 kg/ha/year, respectively. Total cost was 23.9 million VND/ha/year; average income was 86.3 million VND/ha/year; net income was 62.3 million VND/ha/year; profit margin was 2.9. Factors affecting the productivity were survival rate, stocking frequency, tree age and water depth. Profit and profit margin of this model were lower in farms with tree age of 9 years compared to those of younger tree ages. Additionally, profit was affected by productivity of black tiger shrimp, crab, and fish; and stocking density of shrimps and crabs.